An Early Jurassic sauropod tooth from Patagonia (Cañadón Asfalto Formation): implications for sauropod diversity - Carballido, José Luis (2017)
Eusauropods were a group of herbivorous dinosaurs that evolved during the Early Jurassic and dominated the terrestrial ecosystems throughout the Jurassic and Cretaceous. A peak of diversity is represented by the Late Jurassic, when most of the lineages of the derived clade, Neosauropoda, are represented. Different lineages of eusauropods differ in several morphological aspects, including a great diversity in gathering strategies, inferred by their dentition morphology and wear facets. Here we describe a new tooth morphotype that can be well differentiated from any other tooth recovered from the Cañadón Asfalto Formation (Lower?Middle Jurassic). Therefore, this new tooth morphology increases the evidence of a high diversity of sauropods during that time as well as providing evidence of advanced characters in the dentition of some Early Jurassic sauropods (e.g., subcylindrical and narrow crowns with single apical wear facet).